2010
DOI: 10.2987/10-6012.1
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Activity of Lutzomyia shannoni (Diptera: Psychodidae) During Late Season Population Peaks

Abstract: The phlebotomine sand fly, Lutzomyia shannoni (Dyar), is considered both zoophillic and anthropophillic and may be a potential vector of human and livestock pathogens. While the known range of this species in North America has recently been expanded, many aspects of its natural history, which are fundamental components for assessments of disease risk or development of integrated pest management programs for the vector, remain unclear. One is the time of day when individuals are active and searching for blood m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Lutzomyia shannoni (Dyar), the most anthropophilic species in the United States (Young and Perkins 1984), is no exception. Recent detection surveys have expanded the known range of this species northward by several hundred kilometers (Haddow et al 2008, Minter et al 2009) and other studies have revealed some information regarding temporal activity and trap capture of L. shannoni (Brinson et al 1992, Comer et al 1994, Minter et al 2009, Mann et al 2009, Minter 2010, Mann and Kaufmann 2010, Minter and Brown 2010.…”
mentioning
confidence: 98%
“…Lutzomyia shannoni (Dyar), the most anthropophilic species in the United States (Young and Perkins 1984), is no exception. Recent detection surveys have expanded the known range of this species northward by several hundred kilometers (Haddow et al 2008, Minter et al 2009) and other studies have revealed some information regarding temporal activity and trap capture of L. shannoni (Brinson et al 1992, Comer et al 1994, Minter et al 2009, Mann et al 2009, Minter 2010, Mann and Kaufmann 2010, Minter and Brown 2010.…”
mentioning
confidence: 98%
“…Although information on natural history and trapping that could be useful in surveillance has improved (Comer and Brown, 1993;Brinson et al 1992;Comer et al , 1994Haddow et al 2008;Claborn et al 2008;, Mann et al 2009Minter et al 2009Minter et al , 2011Minter 2010;Mann and Kaufmann 2010;Minter and Brown 2010), identiÞcation remains troublesome across this group of insects. Current taxonomic keys to the Phlebotominae are difÞcult to use and are largely based on features of the genitalia and internal reproductive structures, which require the use of tedious clearing, dissection techniques and microscopy, or both (Young and Perkins 1984, Young and Duncan 1994, El-Hossary 2006.…”
mentioning
confidence: 99%